An adaptive observer for a class of nonlinear systems with a high-gain approach. Application to the twin-rotor system. Issue 2 (1st February 2021) - Dimassi, Habib; Hadj Said, Salim; Loria, Antonio; M'Sahli, Faouzi
Abstract : In this paper, we investigate the problem of adaptive observer design for a class of nonlinear systems subject to unknown parameters and such that the classical observer matching assumption is not satisfied. We adopt the idea of generating auxiliary outputs based on a high-gain observer. The estimated auxiliary outputs are then employed by an adaptive observer to reconstruct both states and unknown parameters. The stability analysis is established based on Lyapunov theory. It is shown that the state estimation error and the adaptation error are uniformly bounded and converge to a compact set that may be reduced by an appropriate choice of the design parameters. In order to improve the robustness of our approach against disturbances, the proposed observer is appropriately modified based on sliding modes theory. Theoretical results are illustrated and validated for the twin-rotor MIMO system with numerical simulations.